The Thermosensitive Injectable Celecoxib-Loaded Chitosan Hydrogel for Repairing Postoperative Intervertebral Disc Defect - Du, Yukun; Li, Jianyi; Tang, Xiaojie; Liu, Yingying; Bian, Guoshuai; Shi, Jianzhuang; Zhang, Yixin; Zhao, Baomeng; Zhao, Hongri; Sui, Kunyan; Xi, Yongming (Frontiers in Bioengineering and Biotechnology, 2022)
Percutaneous endoscopic lumbar discectomy has been widely used in clinical practice for lumbar spine diseases. But the postoperative disc re-herniation and inflammation are the main reason of pain recurrence after surgery. The postoperative local defect of intervertebral disc will lead to the instability of spine, to further aggravate the process of intervertebral disc degeneration. In this work, we successfully synthesized the thermosensitive injectable celecoxib-loaded chitosan hydrogel, and investigated its material properties, repair effect, biocompatibility and histocompatibility in vitro and vivo study. In vitro and vivo, the hydrogel has low toxicity, biodegradability, and good biocompatibility. In animal experiment, this composite hydrogel can effectively fill local tissue defects to maintain the stability on spine, delay the process of intervertebral disc degeneration after surgery. These results indicated that this composite hydrogel will be a promising way to treat postoperative intervertebral disc disease in future clinical application.